2018
DOI: 10.1590/1678-5150-pvb-5376
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory evaluation of brachycephalic syndrome in dogs

Abstract: Brachycephalic syndrome (BS) in dogs is characterized by the combination of primary and secondary upper respiratory tract abnormalities and may result in significant upper airway obstruction. It can trigger inspiratory dyspnea, culminating in secondary respiratory distress, soft tissue edema, upper airway obstruction, turbulent airflow, inspiratory noise, and even death. These changes lead to increased resistance of the air passages, which can cause elevation of pulmonary pressure and clinical manifestations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 22 publications
2
33
1
1
Order By: Relevance
“…Furthermore, the E' sept measurement results in the present study were lower than the lateral TDI annulus measurement results reported in brachiocephalic dogs (French Bulldog, n = 22). 17 Similarly, there are some reports of septal mitral annulus measurements being lower than lateral mitral annulus measurements in both human and dog studies. 18,54,55,56 This condition may be explained by the fact that the ventricular septum is rooted in the right ventricle and heart base (aortic and pulmonary roots) and is not able to move around as much as the left ventricle free wall.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the E' sept measurement results in the present study were lower than the lateral TDI annulus measurement results reported in brachiocephalic dogs (French Bulldog, n = 22). 17 Similarly, there are some reports of septal mitral annulus measurements being lower than lateral mitral annulus measurements in both human and dog studies. 18,54,55,56 This condition may be explained by the fact that the ventricular septum is rooted in the right ventricle and heart base (aortic and pulmonary roots) and is not able to move around as much as the left ventricle free wall.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, after the improvement of pulmonary hypoxia, and consequently a decrease in afterload, there is less pulmonary resistance, improving the speed and pressure gradient of the pulmonary flow (Abd El-Moneim et al, 2009). Knowing that the development of pulmonary vascular lesions related to cor pulmonale and mainly to brachycephalic syndrome is slow and chronic (Canola et al, 2018), the age of the animals and the short study period may have been crucial for the non-observation of other changes in the assessment indexes of the right ventricle. Therefore, further studies in this area are recommended.…”
Section: Discussionmentioning
confidence: 99%
“…The brachycephalic animals in the present study were not selected based on a diagnosis of brachycephalic obstructive airway syndrome (BOAS) nor was blood oxygen measured. However, it is important to consider the high prevalence of BOAS in brachycephalic breeds (Packer et al, 2015) and the lower partial pressure of oxygen in the arterial blood compared to nonbrachycephalic dogs even in systemically healthy brachycephalic dogs, attributable to hypoventilation due to morphological characteristics (Hoareau et al, 2012;Canola et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The popularity of canine brachycephalic breeds is rising in many countries (Fawcett et al, 2019). However, brachycephalic dogs are predisposed to inherited conformational disorders, which can result in lower blood oxygen (Packer et al, 2015;Canola et al, 2018) and even systemically healthy brachycephalic dogs were prone to have lower blood oxygen levels (Hoareau et al, 2012). Another characteristic of brachycephalic breeds is a high susceptibility to dystocia, with reports of caesarean indices higher than 80% (Bergstrom et al, 2006;Evans and Adams, 2010).…”
Section: Introductionmentioning
confidence: 99%